The partition of Kosovo and Metohija: Reality or delusion? - Proroković Dušan (Војно дело, 2022)
Although the topic of dividing Kosovo and Metohija into the Serbian and Albanian part was mostly avoided by officials, both national and international, it has been discussed in public since the 1960s, mostly owing to Dobrica Ćosić. By choosing the concept of "demarcation" as "the final solution" during the negotiations between Belgrade and Priština from 2018, the thinking about partition has been reaffirmed. At one point, the highest officials of the Republic of Serbia have announced that the idea represents an official position. However, there are four problems with this approach. Firstly, this concept has never been concretized at the official level. The proposals by Branislav Krstić and Dušan Bataković were probably considered, but not adopted as a part of the Serbian state strategy. Secondly, there was no preparation of the public for such an outcome or that work was sloppily done at the moment when the proposal, at least in principle, was declared official. Hence, the "shallow support" was relative, which is why the legitimacy of the idea was questioned. Thirdly, there are no serious indications that the Albanian party is interested in such an outcome. The attitude of politicians, their readiness to discuss this topic is not well accepted by the Albanian public, thus such a course of action is disputed. Even if a consensus was reached in the negotiations and some kind of agreement was signed with such content, it would remain open how long-term it would be and what consequences there would be in the future. The indications that demarcation can be considered are conditioned in such a way that it would actually represent essential delimitation, exchange of territories, with the accompanying request to continue the process of enlarging the Albanian ethno space. Fourthly, there is no agreement of international factors to carry out something like that. Also, when certain proposals were finally considered and "leaked to the public", they were in line with what the Albanian party was asking for and largely respected the Albanian interests. In the current format of negotiations, and in accordance with the position of the key Western countries responsible for the current situation in Kosovo and Metohija, the implementation of the concept of demarcation cannot have positive effects for Serbia, viewed from a short or long-term perspective whatsoever. The path to the partition of Kosovo and Metohija, just when such a concept would be accepted by international actors as a solution, is full of uncertainty and ambiguity. It is difficult to report such an idea without many consequences after its execution. If partition is to be considered as a solution, long and thorough preparation is necessary, taking into account all its aspects including the new territorial reconfiguration of the postYugoslav space, the implications for regional relations, security and stability.